Factors Affecting the Adoption of Electronic Data Reporting and Outcomes Among Selected Central Cancer Registries of the National Program of Cancer Registries. (2021) - Tangka, Florence K. L.; Edwards, Patrick; Pordell, Paran; Wilson, Reda; Blumenthal, Wendy; Jones, Sandy F.; Jones, Madeleine; Beizer, Jenny; Bernacet, Amarilys; Cole-Beebe, Maggie; Subramanian, Sujha
Abstract : PURPOSE: The CDC's National Program of Cancer Registries has expanded the use of electronic reporting to collect more timely information on newly diagnosed cancers. The adoption, implementation, and use of electronic reporting vary significantly among central cancer registries. We identify factors affecting the adoption of electronic reporting among these registries. METHODS: Directors and data managers of nine National Program of Cancer Registries took part in separate 1-hour telephone interviews in early 2019. Directors were asked about their registry's key data quality goals; staffing, resources, and tools used to aid processes; their definition and self-perception of electronic reporting adoption; key helpers and challenges; and cost and sustainability implications for adoption of electronic reporting. Data managers were asked about specific data collection processes, software applications, electronic reporting adoption and self-perception, information technology infrastructure, and helpers and challenges to data collection and processing, data quality, and sustainability of approach. RESULTS: Larger registries identified organizational capacity and technical expertise as key aides. Other help for implementing electronic reporting processes came from partnerships, funding availability, management support, legislation, and access to an interstate data exchange. Common challenges among lower adopters included lack of capacity at both registry and data source levels, insufficient staffing, and a lack of information technology or technical support. Other challenges consisted of automation and interoperability of software, volume of cases received, state political environment, and quality of data received. CONCLUSION: Feedback from the formative evaluation yielded several useful solutions that can guide implementation of electronic reporting and help refine the technical assistance provided to registries. Our findings may help guide future process and economic evaluations of electronic reporting and identify best practices to strengthen registry operations.